A história das reformas curriculares da rede federal: avanços e retrocessos na integração curricular do CEFET/RJ - Costa, Samantha Rodrigues de Oliveira Vercoza (2023)
The present thesis aimed to analyze the contradictions of human formation evidenced by the conquests, challenges, threats and setbacks of the school curriculum in the Federal Education, focusing on the trajectory of the articulation (juxtapositionintegration-fragmentation) of the curriculum from High School to Professional Education in Technical Course in Mechanics at the Federal Center for Technological Education Celso Suckow da Fonseca, CEFET/RJ. In this approach, we go through the structured reforms since Law n. 5.692/1971, passing through Decree-Laws n. 2.208/1997 and n. 5.154/2004 and reaching Law n. 13.415/2017. We analyze curricular institutionalization-materialization, in dialogue with Sacristán (2013), Lima (2016) and Kuenzer (1999), and the repercussions of educational reforms in the Federal Education. To do so, we outlined this trajectory from five phases and four pedagogical models, which structure our historiographic effort, theoretically guided by Marxist thought and empirically based on bibliographic elements, documentary sources and direct observation of the research object, through the reports of the subjects of the management-teaching-learning process. The documentary investigation allowed delineating the historical trajectory of the curricular organizations constituted by the curricular components and their workloads of general education (High School) and technical education (Technical Course in Mechanics) over the periods. In direct contact with the subjects (teachers, managers and students), thanks to the interviews, we evidenced the various dilemmas and most current challenges that affect the educational institution in its crossing through educational reforms and how these changes defined and redefined in advance and in retrogression the social function of the educational institution. Upon concluding the stages presented by the investigation, the following periodization related to CEFET/RJ was evidenced, from the historiographic point of view: correctional-welfare (1909 to 1942); taylorist-fordist (1942 to 1978); technological-fragmentary (1978 to 2004); technological-integrated (2004 to 2013) and technological-fragmentary (2014-2021). Faced with the comings and goings of changes in the school curriculum at the institution in question, we identify the metamorphosis in the right to work and education. Furthermore, we consider that the recent phase of the technological model, sometimes integrated, sometimes fragmented, has been posing and replacing the dilemmas of the institution that needs to respond to the crisis of fordism and employment, the crisis of the State and public funding. In this compass, CEFET/RJ, in particular, and the Federal Education, in general, must, without losing its traditional quality, assume an even more emancipatory and inclusive aspect with the strengthening of its identity as an institution of integral human formation, without giving up the pressures of generalized verticalization, curricular fragmentation or financial self-sustainability.